2012
DOI: 10.1007/s00128-011-0515-5
|View full text |Cite
|
Sign up to set email alerts
|

Detections of the Neonicotinoid Insecticide Imidacloprid in Surface Waters of Three Agricultural Regions of California, USA, 2010–2011

Abstract: Seventy-five surface water samples were collected from three agricultural regions of California and analyzed for the neonicotinoid insecticide imidacloprid. Samples were collected during California's relatively dry-weather irrigation seasons in 2010 and 2011. Imidacloprid was detected in 67 samples (89%); concentrations exceeded the United States Environmental Protection Agency's chronic invertebrate Aquatic Life Benchmark of 1.05 μg/L in 14 samples (19%). Concentrations were also frequently greater than simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
130
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(135 citation statements)
references
References 5 publications
2
130
2
1
Order By: Relevance
“…Neonicotinoids are frequently found in surface waters Main et al, 2014;Morrissey et al, 2015;Starner and Goh, 2012;Van Dijk et al, 2013), and Imidacloprid and Thiamethoxam were detected in the present study. While the Chemcatcher was not originally designed to collect compounds with log K OW b 2 (Kingston et al, 2000), successful sampling of more polar compounds with an SDB-RPS Empore disk as the receiving phase was reported previously (Stephens et al, 2005;Tran et al, 2007;Vermeirssen et al, 2008), and compounds with log K OW b 2 were also accumulated in quantifiable amounts by the Chemcatchers in the present study (Tables 1 and 2).…”
Section: Concentration-response Dependence and Compounds Responsible mentioning
confidence: 54%
“…Neonicotinoids are frequently found in surface waters Main et al, 2014;Morrissey et al, 2015;Starner and Goh, 2012;Van Dijk et al, 2013), and Imidacloprid and Thiamethoxam were detected in the present study. While the Chemcatcher was not originally designed to collect compounds with log K OW b 2 (Kingston et al, 2000), successful sampling of more polar compounds with an SDB-RPS Empore disk as the receiving phase was reported previously (Stephens et al, 2005;Tran et al, 2007;Vermeirssen et al, 2008), and compounds with log K OW b 2 were also accumulated in quantifiable amounts by the Chemcatchers in the present study (Tables 1 and 2).…”
Section: Concentration-response Dependence and Compounds Responsible mentioning
confidence: 54%
“…EFSA (2008) thus admits: BOverall it is concluded that a high risk for aquatic organisms is indicated for the representative uses in orchards and tomatoes requiring substantial risk mitigation measures to reduce spray drift and runoff. BImidacloprid surface water concentrations (n=21) were reported for six countries across the EU, with concentrations reaching up to >200 μg/L (Mohr et al 2012;Starner and Goh 2012) and 28.6 % of all MIC SW exceeding the RAC SW ; these findings, again, challenge the overall protectiveness of the pre-authorization regulatory risk assessment in the EU.…”
Section: Case Studies: Eu Regulatory Risk Assessments For Bifenthrin mentioning
confidence: 80%
“…Given the widespread usage of neonicotinoids, it is not surprising that these compounds are increasingly detected in various environmental matrices. For example, a recent study published in BECT reported that 89% of the surface water samples collected from three agricultural regions in California contained imidacloprid, and 19% of the samples had imidacloprid concentrations that exceeded the USEPA risk threshold for aquatic life of 1.05 µg/L (Starner and Goh 2012). It has also been reported that the occurrence of neonicotinoids in surface water at environmentally relevant concentrations can negatively affect the physiology and survival rates of freshwater and marine animal species (Pisa et al 2015).…”
mentioning
confidence: 99%